Effect of wheat straw biochar addition on canola growth in different soils - Masooma Hassan; Vladimir Strezov (PLoS ONE, 2025)
Biochar has been demonstrated as a soil amendment to improve soil health and plant yield. The present study aimed at investigating the potential of wheat straw biochar on canola morphology and yield grown in different soils. The influence of biochar on soil physical and chemical properties was also assessed. A completely randomised design pot experiment was carried out in glasshouse where canola was planted in eight different soils with and without biochar treatment. Wheat straw biochar was incorporated in pots at 1% of the total soil weight. Canola was grown for 105 days after which its morphological and yield parameters were evaluated. Analysis of variance confirmed that biochar exerted a significant effect on shoot length, shoot and root dry weights, flower count and 100 seeds weight. Soil texture also affected canola growth and yield parameters with higher clay content in clay loam resulting in less yield compared to others. Biochar also led to improved leaf fresh and dry weight, shoot and root dry weight in loam with lower seeds weight. The seeds weight was the greatest in sandy clay loam, silty clay and silty clay loam which could be ascribed to pH changes, soil texture, decline in soil particle density and improved nutrient availability. Biochar also inflluenced increase in carbon, nitrogen and potassium levels which all helped in maximizing the yield.